Femtosecond laser microfabrication of a fully-integrated optofluidic device for 3D imaging flow cytometry - Federico Sala; Petra Paiè; Alessia Candeo; Francesco Ceccarelli; Roberto Osellame; Andrea Bassi; Francesca Bragheri (Scientific Reports)
Abstract In recent years imaging flow cytometry (IFC) is gaining increasing attention as it combines the characteristics of conventional flow cytometry with optical microscopy techniques, allowing for high-throughput, multi-parameter screening of single cell populations. In the field of biology, the always increasing demand for high content morphological and spatial information led to the development of systems for volumetric imaging. However, current 3D IFC systems are often limited by the incompatibility with available microfluidic devices or by instrumental complexity that might lead to optical misalignment or mechanical instabilities in day-by-day operation. To this end, here we demonstrate the importance of advancing the laser fabrication technique by reporting on a fully integrated optofluidic platform composed of a borosilicate glass chip encompassing reconfigurable integrated photonic circuits for patterned light generation, bonded to a fused silica glass chip incorporating cylindrical hollow lenses, for light-sheet illumination, perfectly aligned to a microchannel where the sample under investigation flows. The system is capable of high-resolution imaging flow cytometry by implementing structured light sheet microscopy in a heterogeneously integrated platform with unprecedented stability. All the components are realized by femtosecond laser irradiation followed by chemical etching. The extreme level of integration permitted by the advanced optimization of the laser fabrication technique allowed the reduction of the assembled components and the absence of moving parts, thus ensuring durable alignment as well as mechanical and thermal stability both in short and long-term operation of the device, for the automated fluorescence signal acquisition during the sample flow.